Potentially Inappropriate Medications in Belgrade, Serbia Nursing Home Residents: A Comparison of Two Approaches. Issue 2 (June 2021) - Stojanović, Marko; Vuković, Milica; Jovanović, Milan; Dimitrijević, Srđan; Radenković, Miroslav
There is currently limited information on the comparative effectiveness of the European Union(7)-potentially inappropriate medication (EU(7)-PIM) list and the Beers criteria for screening PIMs, of which PIMs are a significant concern, in the geriatric population of nursing home residents. This study aims to determine and compare the rates of PIMs detected with the Beers criteria (five sections of which the first is a list of inappropriate medications in older adults) and the EU(7)-PIM list (based on the first section of the Beers criteria). The study, conducted in Gerontology Center Belgrade ( n = 427), is retrospective and observational. The EU(7)-PIM list detected 876 PIMs, while the first section of the Beers criteria detected 782 PIMs (1, 803 with all five sections). The majority of PIMs belong to psychotropic drugs (benzodiazepines being the most common). The EU(7)-PIM list detected significantly more PIMs than the first section of the Beers criteria (2.03 ± 1.63 vs. 1.83 ± 1.27; p = .0005). The number of detected PIMs with both criteria correlates with age, the number of chronic illnesses, the number of medication prescribed, and the comorbidity status. Ultimately, the EU(7)-PIM list detected more PIMs compared to the first section of the Beers criterion.